Экология человека: учебное пособие для вузов - Чубик М. П. Максим Петрович; Абрамова Р. Н. Раиса Николаевна; Болсуновская Л. М. Людмила Михайловна; Баранова А. В. Анастасия Викторовна; Гутарева Н. Ю. Надежда Юрьевна (Томск, Изд-во ТПУ, 2012)
На англ.яз.